The soldiers' general : Bert Hoffmeister at war - Delaney, Douglas E. (Douglas Edward), 1964- (Studies in Canadian military history, 2005)
"Self-doubt so plagued him that he suffered a nervous breakdown even before fighting his first combat action. But by the end of the Second World War, Bert Hoffmeister had exorcised his anxieties, risen from Captain to Major-General, and won more awards than any other Canadian officer in the war. Fighting from the invasion of Sicily in July 1943 to the final victory in Europe in May 1945, this native Vancouverite earned a reputation for being a fearless commander on the battlefield, one who led from the front, one who led from the front and was well loved by those he commanded. How did he do it?" "The Soldiers' General explains how Hoffmeister conducted his business as a military commander. Douglas Delaney dissects Hoffmeister's numerous battles to reveal how he managed and how he led, how he directed and how he inspired. An exemplary leader, Hoffmeister stood out among his contemporaries not so much for his technical ability to move the chess pieces well as for his ability to get the chess pieces to move themselves."--Jacket.